SPIRITUAL HABITATION MODEL IN IMPLEMENTING MORAL AND RELIGIOUS VALUES IN EARLY CHILDREN - Nur Hafidz; Sri Rahayu; Rilih Walid Prihatin (Khatulistiwa, 2023)
Every child has different basic spiritual needs that must be met in life. If spiritual needs are met, it will create peace, tranquility, and security in the lives of children in their families. BIMS Purwokerto Kindergarten as an early childhood education institution takes a strategic role. From here, this research focuses on the strategic model of spiritual habituation in inculcating moral and religious values in early childhood. This research uses field research or analysis data according to the phenomenon with the description. The data collection technique is through observation, in-depth interviews, and documentation. Observations and interviews with teachers, parents, and class A students at BIMS South Purwokerto Kindergarten, Banyumas Regency. While the documents are archives, anecdotal notes, photos, and other works related to the model of children's spiritual habituation. The results of this study focus on the model of spiritual habituation in inculcating moral and religious values through four points, namely; (1) spiritual habituation through programmed, (2) spiritual habituation through routine activities, (3) spiritual habituation through spontaneous, and (4) spiritual habituation through example. These four are the success of the early childhood spiritual habituation model with the development of children's religious abilities (knowing the religion they follow, compassion for fellow creatures of God, imitating worship movements in order and order, recognizing praiseworthy and despicable behavior), respect for tolerance of other religions, knowing Islamic holidays, being able to pray with good ethics, and helping to stimulate spiritual intelligence and other intelligence.